Poland in chains [zbiór znaczków podziemnych] . Polska w kajdanach. Set of unofficial stamps - Poczta Solidarność. (Poczta Solidarność)
Black and red print on white or yellow paper, without perforation. Stamps, with "Poczta Solidarność" imprint, bringing together and patriotic imagery, represent a cross, Jesus and a woman in mourning, accompanied by symbols relating to the national uprisings from 19th century, against an urban landscape. Price: 205 zł per stamp.